Modeling medulloblastoma in vivo and with human cerebellar organoids - Claudio Ballabio (Nature Portfolio, 2020)
Group 3 medulloblastoma (MB) is considered one of the most aggressive forms of this cancer. Here, the authors show that Otx2 and c-MYC oncogenes can drive Group 3 MB formation in mouse and human cerebellar organoids while SMARCA4 overexpression or a EZH2-specific inhibitor can inhibit tumorigenesis.